Nanophotonics Enable Targeted Photothermal Silencing of Nociceptor Neurons (Small 14/2022). Issue 14 (7th April 2022) - Roversi, Katiane; Tabatabaei, Maryam; Desjardins‐Lecavalier, Nicolas; Balood, Mohammad; Crosson, Theo; Costantino, Santiago; Griffith, May; Talbot, Sebastien; Boutopoulos, Christos
Abstract : Nociceptor Neuron Silencing In article number 2103364, Sebastien Talbot, Christos Boutopoulos, and co‐workers report a nanotechnology‐enabled strategy to silence subsets of unmodified nociceptor neurons. It uses laser stimulation of neurons targeted with gold nanoparticles to heat‐activate TRPV1, turning this channel into a cell‐specific entry port for silencing drugs that block neuropeptide release (i.e., communication with other cells). This work establishes a paradigm for interfering with deleterious neuro‐immune interplays.